The Effect of Financial Compensation, Job Stress, and Job Promotion on Employee Performance Through Job Satisfaction at PT. MNC Vision in Central Java - Siregar, Ahmad Surkati; Yanto, Heri; Rozi, Fahrur (Universitas Negeri Semarang, 2019)
The purpose of this study is to examine the effect of financial compensation, job stress, and job promotion through job satisfaction at PT. MNC Vision in Central Java. The method used in this study is a quantitative method using path analysis. The total population in this study is 198 employees at PT. MNC Vision in Central Java which is located in 12 branch offices spreaded in Central Java. The results obtained in this study are financial compensation has a significant effect on employee performance, job promotion has a significance effect on job satisfaction, and job promotion has a significance effect on financial compensation. In addition, from this study also obtained results that job satisfaction and promotion do not have a significance effect on employee performance, while financial compensation and job stress also do not have a significance effect on job satisfaction. Besides, the result shows us that financial compensation and promotion do not have a significance effect on job stress.